Profile of cesarians from a maternity in the interior of Rio Grande do Sul (Research, Society and Development, 2021)
This study aimed to characterize the profile of cesarean sections of a usual risk maternity in the interior of RS. It was carried out by means of a descriptive, retrospective, documentary and quantitative research, which analyzed 1062 medical records of women who had the gestational outcome between the months of June 2018 to May 2019, in a maternity reference of habitual risk, in the interior of Rio Grande do Sul. The analysis was performed statistically to know the frequency and average of the results. Some data were considered relevant for the indication of cesarean sections, such as: age of the patients, parity, gestational age, if there was induction of labor before the indication for cesarean section and the use of technologies for pain relief during labor. It is concluded, from this study, that even with all the support, there are still indications of unnecessary cesarean sections, which can influence both maternal outcomes and neonatal outcomes.